Merkel cell carcinoma in lymph nodes with and without primary origin. (6th February 2022) - Fennig, Shlomit; Landman, Yosef; Brenner, Ronen; Billan, Salem; Fenig, Eyal
Abstract : The prognosis of MCC with lymph node involvement was better in patients with an unknown than a known primary. Treatment with a uniform aggressive combined chemoradiation regimen, with or without lymphadenectomy, led to better survival rates than previously reported.